2003
DOI: 10.1177/000331970305400203
|View full text |Cite
|
Sign up to set email alerts
|

Use of Abciximab and Tirofiban in Patients with Peripheral Arterial Occlusive Disease and Arterial Thrombosis

Abstract: Acute peripheral arterial occlusive disease is an important factor affecting the mobility and mortality rate of elderly patients. Catheter-guided arterial thrombolysis in these patients has its limitations: long lysis times, early occlusions, and high restenosis rates. The study investigated whether the use of tirofiban has the same favorable effect as the glycoprotein (GP) IIb/IIIa receptor antagonist abciximab and whether lysis times can be shortened and the disease course positively influenced by these subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…These agents have been used in peripheral arterial occlusive disease and arterial thrombosis as well 10 11. When used as an adjunct to thrombolysis for peripheral artery thrombosis, some studies have shown that these agents may reduce distal thromboembolism without an increase in haemorrhagic complications 12.…”
Section: Discussionmentioning
confidence: 99%
“…These agents have been used in peripheral arterial occlusive disease and arterial thrombosis as well 10 11. When used as an adjunct to thrombolysis for peripheral artery thrombosis, some studies have shown that these agents may reduce distal thromboembolism without an increase in haemorrhagic complications 12.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were found in patency rates, outcomes, or complications. 26 The economic implications of the addition of GP IIb/IIIa inhibitors to peripheral arterial lysis were examined in the PROMPT (Platelet Receptor Antibodies in Order to Manage Peripheral Artery Thrombosis) Trial population. Seventy patients receiving urokinase thrombolytic infusions for peripheral arterial occlusions were randomized to receive either abciximab or placebo.…”
Section: Prior Applications In Coronary Interventionsmentioning
confidence: 99%
“…Limited prior data suggest that therapy with the platelet glycoprotein (GP) IIb/IIIa receptor inhibitor tirofiban is effective and well tolerated by patients with PAD undergoing peripheral arterial angiography and revascularization. 7 However, it remains unclear whether patients with NSTE ACS and PAD treated with GP IIb/IIIa receptor antagonists and inva-sive management strategies would have favorable outcomes. Therefore, we undertook the present analysis from the Treat angina with Aggrastat and determine Cost of Therapy with an Invasive or Conservative Strategy (TACTICS) Thrombolysis in Myocardial Infarction (TIMI) 18 trial, 8 to assess the benefits and tolerability of GP IIb/IIIa receptor antagonism together with early invasive management among patients with PAD and NSTE ACS.…”
Section: Introductionmentioning
confidence: 99%